POSTPARTUM DEPRESSION IN THE FIRST-TIME MOTHER – CASE REPORT - Sari , Dewi Kartika; Claudia, Claudia; Dewi, Novrida Ratna; Balindra, Fredlina Rossa; Karima, Aziza Matinu (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2026)
Introduction: The transition to motherhood can be challenging due to physical, psychological, and social changes, making women vulnerable to PPD. Routine screening for PPD is essential to facilitate timely intervention and support for affected mothers. This case report aimed to explore the impact of postpartum depression in first-time mothers and the effectiveness of interventions and social support in managing the condition. Methods: This is a qualitative study with a case report method. The study utilized the Edinburgh Postnatal Depression Scale (EPDS) as a screening tool for PPD and involved interventions related to breastfeeding issues and social support. Results: After two weeks, the EPDS test result shows improvement, and the mother also reported increased breastfeeding, with the baby achieving ideal weight and height according to the WHO growth chart. Intervention included open communication, social support, intervention for breastfeeding difficulties, and spousal involvement in childcare. Discuss: Postpartum depression is a strong risk factor for more severe psychological disorders, such as postpartum psychosis, requiring early diagnosis to provide adequate support and prevent further complications. Conclusion: The study highlights the importance of early PPD detection through tools like the EPDS and the crucial role of social support, particularly from the husband, in mitigating PPD risk. It concludes by emphasizing the need for ongoing research to develop effective interventions for managing postpartum depression in primiparous mothers. Keywords: postpartum depression, primiparous, social support.